Neurological Associations of COVID-19—Do We Know Enough: A Tertiary Care Hospital Based Study - Kushwaha, Suman; Seth, Vaibhav; Bapat, Prateek; R, KiranGowda; Chaturvedi, Monali; Gupta, Renu; Bhattar, Sonali; Maheshwari, Siddharth; Anthony, Aldrin (Frontiers in Neurology, 2020)
The neurotrophic potential of SARS-CoV-2 virus is manifesting as various neurological disorders in the present pandemic. Nervous system involvement can be due to the direct action of the virus on the brain tissue or due to an indirect action through the activation of immune-mediated mechanisms. This study will discuss the detailed systematically evaluated clinical profile and relevant investigations and outcome of fourteen laboratory confirmed SARS- CoV-2 positive patients presenting with neurological signs and symptoms. The patients were further categorised into confirmed, probable and possible neurological associations. The probable association was found in meningoencephalitis (n-4), stroke (n-2), Guillain-Barré syndrome (n-1), anosmia (n-1). The other six patients had coexisting neurological diseases with SARS-CoV-2. Patient with a large artery stroke succumbed to the illness due to respiratory complication . Memory impairment as a sequela is present during follow up of one encephalitis patient. Presently the early recognition and diagnosis of neurological manifestations remains a challenge for clinicians as the SARS- CoV-2 related neurological manifestations are in evolution. The long term correlation study of clinical profile, radiological and laboratory investigations along with neuropathological studies is needed to further understand the pathophysiology behind the SARS-CoV-2 neurological manifestations. Further understanding will facilitate in timely recognition, therapeutic intervention and possible prevention of long term sequalae.